Pengaruh Teman Sebaya Dengan Praktik Seksual Pranikah Remaja Pria Urban Sulawesi Selatan - Muchlisa, Nurul; Putri Bausad, Aynun Abdi (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2023)
The estimated number of adolescents in the world is 1.2 billion with 85% living in developing countries. The high level of premarital sexual activity in developing countries is still a problem today because it is closely related to the impact it causes in the form of HIV AIDS, STIs and others. This study aims to determine the effect of peer pressure on premarital sexual practices in young men aged 15-24 years and not yet married in urban areas of South Sulawesi. This research is a cross-sectional study using the results of data analysis from the 2017 Indonesian Demographic and Health Survey with a total sample of 207 unmarried male youths aged 15-24 years in South Sulawesi. The results of the analysis showed that there was peer influence (p=0.000), age (p=0.000) and substantial influence (p=0.002) with premarital sexual practices. Peers have an influence on premarital sexual practices in young men. Boys encourage other boys to be sexually active even when they are not ready.